Fecundity and Ferocity of the European Peoples: The Reception of Two Classical Topoi in the Res Germanicae (1531) of Beatus Rhenanus - Lampinen, Antti (Pohjois-Suomen Historiallinen Yhdistys, 2025)
This article looks at the reception, in the Res Germanicae of the prominent Alsatian humanist Beatus Rhenanus, of a classical assemblage of literary tropes that portrayed European barbarian groups as naturally prone to over-abundance of fertility as well as intrinsically fierce. In antiquity, the conjuncture of ideas about threatening demographic growth and natural ferocity affected deeply the way that Romans thought about their relationship with the northerners, whether ‘free’ groups or provincials. In Rhenanus’ conception of the early Germanic history, though, the otherwise faithfully followed testimonies of ancient authors have been selectively utilized in this regard. While the motif of ferocity is put into use, the idea of European barbarians’ fecundity is conspicuously avoided. Several explanations connected with Rhenanus’ authorial intentions and historical context are proposed for this factor in classical reception, ranging from the role of the Ottoman threat in the Early Modern European imagination, to the preference for the notion of ancient Germanic martial virtus as an explanatory factor for their successes instead of their numbers. What Rhenanus’ strategies of reception reveal is an open-ended negotiation with the classical inheritance during a very crucial period in the formation of the concept of Europe.